D-Limonene Is a Potential Monoterpene to Inhibit PI3K/Akt/IKK-α/NF-κB p65 Signaling Pathway in Coronavirus Disease 2019 Pulmonary Fibrosis - Yang, Fan; Chen, Ru; Li, Wan-yang; Zhu, Hao-yue; Chen, Xiao-xuan; Hou, Zhen-feng; Cao, Ren-shuang; Zang, GuoDong; Li, Yu-xuan; Zhang, Wei (Frontiers in Medicine, 2021)
At the time of the prevalence of COVID-19, pulmonary fibrosis (PF) related to COVID-19 has become the main sequela. However, the mechanism of pulmonary fibrosis related to coronavirus disease (COVID-PF) is unknown. This study aimed to explore the key targets in the development of COVID-PF and the mechanism of D-limonene in the COVID-PF treatment. The differentially expressed genes of COVID-PF were downloaded from the Genecards database and their pathways were analyzed. D-limonene was molecularly docked with related proteins to screen its pharmacological targets, and a rat lung fibrosis model was established to verify D-limonene's effect on COVID-PF-related targets. The results showed that the imbalance between collagen breakdown and metabolism, inflammatory response and angiogenesis are the core processes of COVID-PF, and PI3K/AKT signaling pathways are the key targets of treatment of COVID-PF. The ability of D-limonene to protect against PF induced by bleomycin in rats was reported. The mechanism is related to the binding of PI3K and NF-κB p65, and the inhibition of PI3K/Akt/IKK-α/NF-κB p65 signaling pathway expression and phosphorylation. These results confirmed the relationship between the PI3K-Akt signaling pathway and COVID-PF, showing D-limonene has potential therapeutic value for COVID-PF.